Bloom : a memoir - Hampton, Kelle (William Morrow, 2013)
"The author of the popular blog Enjoying the Small Things interweaves lyrical prose and stunning four-color photography as she recounts the story of the first year of her daughter Nella--who has Down syndrome--and celebrates the beauty found in the unexpected, the strength of a mother's love, and, ultimately, the amazing power of perspective"--